Density of slates based on dimensional dilution symmetry for disordered hypercubic lattices - Domínguez, Daniel; Wiecko, C. (Comisión Nacional de Energía Atómica; Argentina)
Fil: Domínguez, Daniel Comisión Nacional de Energía Atómica; Argentina